The Boundedness of Bilinear Singular Integral Operators on Sierpinski Gaskets (Analysis in Theory and Applications, 2018)
In the paper we give the boundedness estimate of bilinear singular integral operators on Sierpinski gasket inspired from [1].
Keywords: boundedness; bilinear singular integral; Sierpinski gaskets.